Clinical Manifestations of Primary Spontaneous Pneumothorax in Pediatric Patients: An Analysis of 78 Patients - Chung-Hsein Shih; Hsiu-Wen Yu; Ya-Chun Tseng; Yu-Ting Chang; Chin-Ming Liu; Jen-Wen Hsu (Pediatrics and Neonatology)
The aims of this investigation were to explore primary spontaneous pneumothorax (PSP) in pediatric patients and to evaluate the clinical manifestations and outcomes of the PSP. Methods: Seventy-eight patients diagnosed with PSP between January 2004 and December 2009 was retrospectively studied. The clinical data on demographics, diagnostic imaging, therapeutic approach, and outcomes were collected and analyzed. Results: The sex ratio of 78 PSP patients was 7.7:1 (male:female=69:9), and the age distribution concentrated between 15 years and 18 years (66 patients, 84.6%). The most common presenting symptom was chest pain (69 patients, 88.5%). The average body mass index was 18.2±1.6 (n=66). Autumn was the more likely attack season for PSP in this study (p=0.005). Twenty-eight patients (35.9%) had tension pneumothorax. Only nine (11.5%) patients had a past history of cigarette smoking. All 21 outpatients received supportive treatment. Out of 57 inpatients, 10 (17.5%) received oxygen therapy, 39 (68.4%) received closed-tube drainage, and 6 (10.5%) received video-assisted thoracoscopic surgery. Apical bleb and subpleural bullae formation were common pathological findings (21 patients, 91.3%). Twenty-four (42.1%) patients experienced a second attack, and six (10.5%) patients had a third attack. Conclusion: Pediatric PSP occurred mainly in boys of the late teenage group with lower body mass index. Autumn was the most likely attack season. There was only a small portion of the patients who smoked. There was no evidence to find a correlation between smoking and pediatric PSP attacks. Length of stay was shorter in supportive treatment and closed-tube drainage patients than that in video-assisted thoracoscopic surgery–treated patients. The outcomes were satisfactory.